Dietary prophage inducers and antimicrobials: toward landscaping the human gut microbiome. (3rd July 2020) - Boling, Lance; Cuevas, Daniel A.; Grasis, Juris A.; Kang, Han Suh; Knowles, Ben; Levi, Kyle; Maughan, Heather; McNair, Katelyn; Rojas, Maria Isabel; Sanchez, Savannah E.; Smurthwaite, Cameron; Rohwer, Forest
ABSTRACT: The approximately 10 11 viruses and microbial cells per gram of fecal matter (dry weight) in the large intestine are important to human health. The responses of three common gut bacteria species, and one opportunistic pathogen, to 117 commonly consumed foods, chemical additives, and plant extracts were tested. Many compounds, including Stevia rebaudiana and bee propolis extracts, exhibited species-specific growth inhibition by prophage induction. Overall, these results show that various foods may change the abundances of gut bacteria by modulating temperate phage and suggests a novel path for landscaping the human gut microbiome.